Natural materials for food packaging application - Parameswaranpillai, Jyotishkumar (Wiley-VCH, 2023)
Packaging plays an essential role in the production of food and its movement through the global supply chain. Food packaging has been a significant site of innovation recently, allowing consumers better access to natural and organic foods, extended shelf lives, and more. However, food packaging has become an increasingly serious environmental hazard, with the result that biodegradable food packaging has become a vital and growing area of research. Natural Materials for Food Packaging Application provides a thorough and detailed introduction to natural packaging and its applications in food transportation. Treating both recent innovations and prospective future developments, it provides readers with extensive insights into the current state of research in this field. The result is a volume designed to meet the aspirational needs of a sustainable food industry. Natural Materials for Food Packaging Application readers will also find: Detailed treatment of biodegradable packaging materials including thermo-plastic starch, polybutylene succinate, and more; Discussion of subjects including chitosan-based food packaging films, clay-based packaging films, and more; and An authorial team with vast expertise in the field of biological polymer production.